How much is new information worth? Evaluating the financial benefit of resolving management uncertainty. Issue 1 (10th December 2014) - Maxwell, Sean L.; Rhodes, Jonathan R.; Runge, Michael C.; Possingham, Hugh P.; Ng, Chooi Fei; McDonald‐Madden, Eve; du Toit, Johan
Summary Conservation decision‐makers face a trade‐off between spending limited funds on direct management action, or gaining new information in an attempt to improve management performance in the future. Value‐of‐information analysis can help to resolve this trade‐off by evaluating how much management performance could improve if new information was gained. Value‐of‐information analysis has been used extensively in other disciplines, but there are only a few examples where it has informed conservation planning, none of which have used it to evaluate the financial value of gaining new information. We address this gap by applying value‐of‐information analysis to the management of a declining koala Phascolarctos cinereus population. Decision‐makers responsible for managing this population face uncertainty about survival and fecundity rates, and how habitat cover affects mortality threats. The value of gaining new information about these uncertainties was calculated using a deterministic matrix model of the koala population to find the expected population growth rate if koala mortality threats were optimally managed under alternative model hypotheses, which represented the uncertainties faced by koala managers. Gaining new information about survival and fecundity rates and the effect of habitat cover on mortality threats will do little to improve koala management. Across a range of management budgets, no more than 1·7% of the budget should be spent on resolving these uncertainties. The value of information was low because optimal management decisions were not sensitive to the uncertainties we considered. Decisions were instead driven by a substantial difference in the cost efficiency of management actions. The value of information was up to forty times higher when the cost efficiencies of different koala management actions were similar. Synthesis and applications. This study evaluates the ecological and financial benefits of gaining new information to inform a conservation problem. We also theoretically demonstrate that the value of reducing uncertainty is highest when it is not clear which management action is the most cost efficient. This study will help expand the use of value‐of‐information analyses in conservation by providing a cost efficiency metric by which to evaluate research or monitoring.